Independent Foot Care Implementation for Patients with Type II Diabetes Mellitus - Maria Kornelia Ringgi Kuwa; Gabriel Mane; Mediatrix Santi Gaharpung; Maria Agustina Soy; Siti Aisyah (GLOBAL HEALTH SCIENCE GROUP, 2024)
Food care is a practice for individuals with normal or high blood sugar levels, performed regularly to maintain personal hygiene, especially to kill or inhibit the growth of germs/ bacteria on the skin and other body tissues. Proper food care aims to educate diabetes Mellitus patients about the risk factors for diabetic wounds and reduce the incidence of complications among high-risk patients. Objective to examine and implement independent foot care for patients with type II diabetes mellitus. This study employed a case study design with a single respondent. Data were collected using interview sheets to evaluate the outcomes. The findings indicate that implementing independent foot care is highly effective. According to the researcher’s observations, this intervention helps prevent complications such as gangrene. Post-treatment results showed significant improvements: the respondent’s feet appeared clean and moisturized, nails were neatly trimmed, calluses were reduced, and overall foot health was enhanced.